Physiological genital discharge. - Núñez Vidalón, Ricardo (2015)
I must be Physiological genital discharge, that is considered normal flow, and raised the things we slip inadvertently to always arduous field boundary between normality and abnormality, between the physiological and pathological. Normality is an idealized conventional concept in practice can only exceptionally shown.